2017
DOI: 10.1371/journal.pone.0177022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hepatitis C virus infection in two adjacent Thai provinces with drastically different seroprevalence

Abstract: Improved awareness of the hepatitis C virus (HCV) transmission has contributed to the overall decline in the HCV infection rate in some developing countries including Thailand. Chronic HCV infection in some rural Thai communities, however, presents a challenge in the efforts to treat and manage HCV-related diseases. Published and unpublished studies have suggested an unusually high incidence of HCV infection in a Thai province of Phetchabun compared to elsewhere in Thailand. To determine the magnitude of HCV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…This follow-up study examined the prevalence and genotypes of HCV found in Petchabun and Khon Kaen province and comprised part of a previous HCV surveillance project involving 3,077 samples from high- and average-level HCV-endemic areas ( Wasitthankasem et al, 2017 ). All HCV-seropositive individuals were informed of their status and invited to participate in confirmatory testing for HCV infection using anti-HCV, HCV Ag, and HCV RNA assays combined with liver enzyme levels and liver stiffness tests in March 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This follow-up study examined the prevalence and genotypes of HCV found in Petchabun and Khon Kaen province and comprised part of a previous HCV surveillance project involving 3,077 samples from high- and average-level HCV-endemic areas ( Wasitthankasem et al, 2017 ). All HCV-seropositive individuals were informed of their status and invited to participate in confirmatory testing for HCV infection using anti-HCV, HCV Ag, and HCV RNA assays combined with liver enzyme levels and liver stiffness tests in March 2016.…”
Section: Methodsmentioning
confidence: 99%
“… Anti-HCV reactive samples were collected from individuals who returned to the HCV follow-up study for the treatment program (270 from the previous HCV study and 28 from self anti-HCV screening) ( Wasitthankasem et al, 2017 ). Anti-HCV nonreactive samples were excluded, and reactive samples were tested for liver function enzymes, liver stiffness, HCV RNA level and HCV Ag level.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a part of an overall research project named “Prevalence and Genotypes of Hepatitis C Virus in Phetchabun and Khon Kaen Provinces as a Model for Treatment” [ 8 ]. The inclusion criteria of the overall project were: Phetchabun or Khon Kane residency, generally good health, age between 30 to 64 years, no clinical signs of immunodeficiency disease or HIV infection, and late stage of liver disease (see definition below) or hepatocellular carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria of the overall project were: Phetchabun or Khon Kane residency, generally good health, age between 30 to 64 years, no clinical signs of immunodeficiency disease or HIV infection, and late stage of liver disease (see definition below) or hepatocellular carcinoma. The study protocol set out two independent sample recruitments (one for screening and one for clinical investigation), a serological survey [ 8 ] and follow up to clinical evaluation ( Fig 1 ). Accordingly, most individuals who were positive for anti-HCV in the serosurvey were examined HCV related liver disease in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation